Vibration Suppression of Bolter Miner Employing Dynamic Vibration Absorber - Ang Li; Bukang Wang; Teng Wang; Zhifu Guo; Zhaokun Yan (Shock and Vibration)
The bolter miner is a critical piece of equipment in the rapid set of tunneling equipment, and the load generated during coal cutting may lead to excessive vibration of the equipment and reduce its reliability. In order to reduce the vibration response of the bolter miner, this paper proposes the installation of a dynamic vibration absorber (DVA) inside the cutting arm of the bolter miner. A five-degree-of-freedom dynamics model was developed, and the cutting part was regarded as two rigid bodies flexibly connected by a rotating spring. The model’s accuracy was verified based on the field test results, and the error was within 7%. It was found that the cutting caused the first-order modal vibration, and the DVA was placed in the cavity of the cutting arm to control the modal vibration of this order. To minimize the vibration, a coupled dynamics model between the DVA and bolter miner was developed, and the DVA parameters were optimized. The results showed that the acceleration RMS and peak values of the cutting part were reduced by 12% and 30.1%, respectively; the acceleration RMS and peak values of the main frame were reduced by 6.5% and 17%, respectively, and the fatigue life of the cutting arm was increased by 34.2%.